ANÁLISE POR ELEMENTOS FINITOS DE UM PÓRTICO ROLANTE PARA ELEVAÇÃO DE CARGAS, DE ACORDO COM OS CRITÉRIOS DA NBR 8400: 2019 (Revista Interdisciplinar Pensamento Científico, 2021)
Amid the industry growth over time, companies had to adapt to maximize production. Therefore, there was a need for changes in the way materials is transported, such as overhead cranes and gantries.This study has the purpose of making a structural analysis of a gantry for load lifting, by finite element method, for validation and reliability of the equipment, meeting the criteria of NBR 8400 2019 standard. This analysis was suggested by an oil company, in order to confirm the use of the gantry for the suggested workload. The analyzed gantry has an elevation height and span, both of 4 meters, with a load lifting capacity of up to 3 tons. For the analysis, the method of studying the stresses and deformations in the main beam and legs was used. With this it is possible to carry out, through the Solidsworks program, the necessary simulations to verify if the equipment will be able to support the applied load. With the results obtained through the simulations and the parameters informed by the company, it is possible to validate or not the use of the gantry for load lifting.
Keywords: Load Lifting; material handling; logistics; quality; gantry